Adela paludicolella Zeller, 1850, and Adela orientella Staudinger, 1870 sp. rev. (Lepidoptera, Adelidae): two distinct species revealed by morphological analysis and DNA barcoding - Timossi, Giovanni; Huemer, Peter (Zootaxa, 2025)
The morphological study of A. paludicolella specimens collected in Italy—specifically from the island of Elba (Tuscany) and Sardinia—as well as from Greece, has revealed differences in habitus and reproductive organs between the Italian and Greek specimens. Subsequent genetic analysis confirmed the genetic distinction between A. paludicolella Zeller, 1850, and A. orientella Staudinger, 1870 (sp. rev.), which are distributed in the western and eastern Mediterranean, respectively.